ChemInform Abstract: Synthesis of Naturally Occurring Tropones and Tropolones. Issue 7 (29th January 2015) - Liu, Na; Song, Wangze; Schienebeck, Casi M.; Zhang, Min; Tang, Weiping
Abstract Review: 292 refs.